A study on the ion sound and Langmuir wave system solutions - Elhassanein, A.; Abdou, M. A.; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2025)
In this paper, we investigate new exact solutions of the ionic wave system. We are interested in the case where the system is under the action of the ponderomotive force which results from a nonlinear force that a charged particle encounters in an inhomogeneous oscillating electromagnetic field due to a high-frequency field. New solutions are examined using two different methods. Numerical simulation is used to investigate physical features of solutions. Exact solutions allow researchers to plan and carry out experiments to determine these parameters or functions by creating appropriate natural conditions.
Keywords: Expc function method; exact solutions; ionic sound system; Langmuir waves